Translation and validation of the youth sexual intention questionnaire and self-control scale among adolescents in Indonesia - Desy Ayu Wardani; Siti Khuzaimah Ahmad Sharoni; Endang Triyanto (Universitas Airlangga, 2026)
Introduction: Adolescence is a critical period in sexual decision-making, where sexual intention and self-control play a significant role in preventing risky behaviors. Valid and reliable measurement tools are essential for assessing these psychological constructs within specific cultural contexts. The purpose of this study was to assess the validity and reliability of the Youth Sexual Intention Questionnaire (YSI-Q) and Self-Control Scale among adolescents in Indonesia.Methods: Five experts reviewed two sets of questionnaires. The cross-sectional pilot study was conducted with 403 adolescents. The YSI-Q and Self-Control Scale were translated and culturally adapted following standardized guidelines. The psychometric evaluation included content validity and internal consistency (Cronbach’s alpha).Results: The content validation index of the Indonesian version of the Youth Sexual Intention Questionnaire and Self-Control Scale among adolescents was .900 and 1.000. Internal consistency was strong for YSI-Q (Cronbach’s α = .929) and the Self-Control Scale (Cronbach’s α = .828).Conclusion: The YSI-Q and Self-Control Scale exhibit strong reliability and validity, making them suitable for assessing adolescent sexual intention and self-control in research and clinical settings. Further validation in diverse adolescent subgroups is recommended.Keywords: adolescent, intention, psychometrics